Tinjauan Ekonomi Potensi Pendapatan Asli Daerah Melalui Pembangunan Pembangkit Listrik Tenaga Mikrohidro (PLTMH) - Normansyah Normansyah (entries, 2022)
One of the Renewable Energy potentials that can be developed in Ketapang Regency is Micro Hydro Power Plant (PLTMH) in the form of a Waterfall, which is located in 3 (three) districts, in 5 (five) villages, with an average discharge of 0.1-0 , 2m³ / sec. And along the Pawan River Basin, there is enough potential for Micro Hydro Power Plants. From the economic point of view to help overcome the problem of electricity shortages, especially in rural areas. In an effort to help accelerate the electrification process of Ketapang Regency through rural electrification based on renewable energy sources especially water energy. As well as helping the realization of an Energy Independent Village based on Micro Hydro Power Plants (PLTMH) which is able to improve economic, social, educational and technology introduction aspects in rural areas of Ketapang Regency. This research activity consists of several stages, including: (1). Location Survey, (2). Calculation of Turbine Plan, (3) Economic Review, (4) Report Making. The results showed that, Siduk River Flow has an average available flow of 24 m³ / s and the height of water fall that can be optimized is 8 m, with the potential for electric power reaching 1.3 MW. The planned electrical power in the Siduk PLTMH is 500 kW (2 x 250 kW), with a design discharge (Qd) 2 x 4.75 m³ / s, with an effective fall height (Hn) of 7.6 m. Electricity production per year is 3,066,000 (kwh / year), with an investment of Rp. 16,000,000,000, investment period of 20 years. Pay Back Period (PBP) 3.9 Years, Rate of Return (ROR) 25.43%, Internal Rate of Return (IRR) 25.31%.